Sikap masyarakat terhadap pembangunan ruang terbuka publik Borasi Kabupaten Manokwari - A. Rumainum, Jeanne; Matualage, Amestina; E. S Bless, Aplena (Program Pascasarjana Universitas Papua, 2025)
ABSTRACT: The construction of the Borasi public open space was built with the aim of providing public facilities so that the public can carry out various activities free of charge. This research aims to (1) determine community attitudes regarding the construction of public open spaces in Borasi Manokwari (2) analyze the factors that influence community attitudes regarding the construction of public open spaces. The research method uses a survey which is analyzed descriptively qualitatively for community attitudes towards the development of public open spaces, while for the relationship between factors that influence community attitudes and the development of public open spaces, use an analysis correlation Sperman. The total sample was 37 families directly affected, taken using the census method. The research was carried out for 28 days in February 2024. The results of the analysis showed that the community's attitude towards the construction of the Borasi public open space from cognitive, affective and conative aspects was categorized as agree. The results of analysis correlation Sperman show that the independent variables age (X1), and length of stay (X3) have a real effect on attitude, while education (X2), and income (X4) have no real effect.